2013
DOI: 10.1002/eji.201243089
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase derived reactive oxygen species are involved in human neutrophil IL‐1β secretion but not in inflammasome activation

Abstract: Neutrophils are essential players in acute inflammatory responses. Upon stimulation, neutrophils activate NADPH oxidase, generating an array of reactive oxygen species (ROS).Interleukin-1 beta (IL-1β) is a major proinflammatory cytokine synthesized as a precursor that has to be proteolytically processed to become biologically active. The role of ROS in IL-1β processing is still controversial and has not been previously studied in neutrophils. We report here that IL-1β processing in human neutrophils is depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 41 publications
9
47
2
Order By: Relevance
“…However, there are conflicting results showed the relationship between oxidative stress and NLRP3 inflammasome. Some researches showed that NADPH oxidase-deficient macrophages or neutrophils had normal NLRP3 activation [84][85][86]. The reason leading to the controversial results may due to the different ways of ROS generation.…”
Section: Discussionmentioning
confidence: 93%
“…However, there are conflicting results showed the relationship between oxidative stress and NLRP3 inflammasome. Some researches showed that NADPH oxidase-deficient macrophages or neutrophils had normal NLRP3 activation [84][85][86]. The reason leading to the controversial results may due to the different ways of ROS generation.…”
Section: Discussionmentioning
confidence: 93%
“…Studies show that IL-1β processing in human neutrophils is dependent on caspase-1, elastase, and proteinase 3. It has been shown that NOX2-deficient neutrophils not only activate caspase-1 but also express NALP3, indicating that ROS is neither required for inflammasome activation nor for its priming, as has been reported for macrophages (Gabelloni et al, 2013; Sokolovska et al, 2013). Recent advances have shown that NOX need not be the primary source of ROS production during inflammasome activation.…”
Section: Introductionmentioning
confidence: 85%
“…The results also suggest that redox-regulated processes may be more important to IL-6 and CXCL8 protein synthesis or release, than to the transcriptional activation of their respective genes. Gabelloni and coworkers recently reported a novel role of NADPH-oxidase-derived ROS in IL-1β secretion from neutrophils (Gabelloni et al, 2013). Thus it is tempting to speculate that redox-regulated processes also could affect the secretion of IL-6 and CXCL8.…”
Section: Dep and Other Combustion Particles Contain Varied And Complementioning
confidence: 98%